2023
DOI: 10.1002/adma.202304957
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Construction of Efficient Interfaces Ensures High‐Performance Direct Ammonia Protonic Ceramic Fuel Cells

Fan He,
Mingyang Hou,
Zhiwei Du
et al.

Abstract: Direct ammonia protonic ceramic fuel cells (PCFCs) are highly efficient energy conversion devices since ammonia as a carbon‐neutral hydrogen‐rich carrier shows great potential for storage and long‐distance transportation when compared with hydrogen fuel. However, traditional Ni‐based anodes readily suffer from severe structural destruction and dramatic deactivation after long‐time exposure to ammonia. Here a Sr2Fe1.35Mo0.45Cu0.2O6−δ (SFMC) anode catalytic layer (ACL) painted onto a Ni‐BaZr0.1Ce0.7Y0.1Yb0.1O3−δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Ni et al performed a thermodynamic analysis of an NH 3 -fueled SOFC/PCFC and pointed out that the NH 3 -fueled PCFC was superior to the NH 3 -fueled SOFC in terms of theoretical maximum efficiency . Numerous studies have focused on NH 3 -fueled PCFCs. Pan et al painted an iron catalyst onto the surface of a tubular Ni-BZCYYb anode, as shown in Figure . The PCFC with an iron catalyst layer (denoted as Fe-cell) had a PPD of 685 mW cm –2 at 650 °C in NH 3 , higher than 506 mW cm –2 of the bare cell.…”
Section: Integration Of Thermocatalystsmentioning
confidence: 99%
“…Ni et al performed a thermodynamic analysis of an NH 3 -fueled SOFC/PCFC and pointed out that the NH 3 -fueled PCFC was superior to the NH 3 -fueled SOFC in terms of theoretical maximum efficiency . Numerous studies have focused on NH 3 -fueled PCFCs. Pan et al painted an iron catalyst onto the surface of a tubular Ni-BZCYYb anode, as shown in Figure . The PCFC with an iron catalyst layer (denoted as Fe-cell) had a PPD of 685 mW cm –2 at 650 °C in NH 3 , higher than 506 mW cm –2 of the bare cell.…”
Section: Integration Of Thermocatalystsmentioning
confidence: 99%
“…17 A PCFC with a catalytic layer of Sr 2 Fe 1.35 Mo 0.45 Cu 0.2 O 6− δ (SFMC) on the outer surface of the anode has demonstrated a relatively stable operation at >650 °C; the exsolved Fe and Cu nanoparticles from the SFMC reacted with Ni to create highly active phases of NiCuFe and/or NiFe on the anode surface, resulting in improved performance and stability. 18 However, the relatively poor ammonia decomposition activity and durability at low temperatures (such as 550 °C) remain significant challenges.…”
Section: Introductionmentioning
confidence: 99%